One, two, skip a few! : first number rhymes - Arenson, Roberta (New York : Scholastic, 1999)
Count on fun with these irresistible rhymes old and new, filled with speckled frogs, mischievous monkeys, playful elephants, and many other companions to help you practice your counting skills.
"This edition is only available for distribution through the school market"
Preschool
Keywords: Counting-out rhymes; Counting; Counting -- Poetry